Automatic Plant Watering Based on Fuzzy Decision Support System - Iswanto Suwarno; Anna Nur Nazilah Chamim‬; Cosmin A. Popesc; Bruno Baruque Zanon (Journal of Telecommunication Control and Intelligent System, 2021)
Almost everyone is still doing the activity of watering plants manually, by watering the plants one by one is quite time consuming and a waste of energy. Watering plants is an activity that is always done every day by almost everyone who has plants at home, office and elsewhere. The activity of watering plants manually cannot know how much water the plants need so many plants die from excess water. With the above problems, this paper contributes in designing an automatic plant sprinkler system. With the development of technology, it is easier to water plants. Technological advances include automatic plant watering, automatic plant watering equipment utilizing a microcontroller as the brain circuit that processes the entire circuit to be used for watering plants. The microcontroller is used to read sensor data in the form of a soil moisture sensor. The sensor is processed by the microcontroller using the Fuzzy algorithm. Mamdani's fuzzy knowledge can be used as a reference when the plants are watered or not to take the values ​​of soil moisture and air temperature, so that the needs of aquatic plants can be met. This system can run automatically watering plants when the soil is dry,